Interactive effects of ozone and climate on water use, soil moisture content and streamflow in a southern Appalachian forest in the USA - McLaughlin, S B (The New phytologist, 2007)
* Documentation of the degree and direction of effects of ozone on transpiration of canopies of mature forest trees is critically needed to model ozone effects on forest water use and growth in a warmer future climate. * Patterns of sap flow in stems and soil moisture in the rooting zones of mature trees, coupled with late-season streamflow in three forested watersheds in east Tennessee, USA, were analyzed to determine relative influences of ozone and other climatic variables on canopy physiology and streamflow patterns. * Statistically significant increases in whole-tree canopy conductance, depletion of soil moisture in the rooting zone, and reduced late-season streamflow in forested watersheds were detected in response to increasing ambient ozone levels. * Short-term changes in canopy water use and empirically modeled streamflow patterns over a 23-yr observation period suggest that current ambient ozone exposures may exacerbate the frequency and level of negative effects of drought on forest growth and stream health